Do housing costs eat up all regional income disparities? - Larissa Klick; Sandra Schaffner (ZBW - Leibniz-Informationszentrum Wirtschaft, 2019)
There exists empirical evidence for Germany that income inequality has increased. Further, development of housing prices is quite heterogeneous between regions. In this paper we analyze regional inequality regarding purchasing power per capita. By contrast to the existing literature we apply comprehensive data on the 1x1 km level. Consequently, this very precise delineation gives much better insights into regional disparities also below the level of administrative borders. In accordance with the existing literature we cannot observe increasing regional disparities. Further, first results indicate that there is a strong correlation between purchasing power and housing costs. The regional disparities will be described via inequality measurements and its decomposition. By a strong positive correlation between the price index for house purchases (RWI-GEO-REDX) and purchasing power, a dilution of regional purchase power can be found when taking real estate prices into account. Regional disparities vanish according to the analysis of the small-scale data.
Keywords: J31; R23; R31; 330; Regional Disparities; Housing prices